Analysis of Macroeconomic Factors that Influence the Movement of the Composite Stock Price Index (IHSG) on the Indonesian Stock Exchange for the Period 2013 – 2023 - Uli Septepana; Perdana Lomo Obrien; Aris Febrianta Surbakti; Fuji Astuty; Wenny Anggeresia Ginting (Cita konsultindo, 2024)
This research aims to analyze external macroeconomic factors that influence the IHSG in 2013 - 2023. Independent variables include inflation, interest rates, world oil prices, and the rupiah exchange rate against the US dollar. the dependent variable is the Composite Stock Price Index (IHSG) for 2013 - 2023. The sample consists of 132 observations. The analysis method uses multiple linear regression analysis, analysis and decision making using Eviews 12 software. The test results show that inflation has a positive and insignificant effect on the IHSG, the exchange rate has a negative and significant effect on the IHSG, world oil prices have a negative and insignificant effect on the IHSG, and interest rates. Interest has a significant positive influence on the IHSG.